On the modeling of the controlled groundwater flow in a soil column - Polyakov, V. L. (Reports of the National Academy of Sciences of Ukraine, 2016)
The analytical solutions of the problems of draining and wetting a soil column are got with regard for the aeration zone on the filtration. The filtration characteristics for three classes of fine-dispersed soils are obtained. Simplifying the description of the water exchange between two characteristic zones is shown to cause essential errors in calculations.